President’s Message: Feedback - Success of an Organization - Stephens, Gloria (Operating Room Nurses Association of Canada Journal, 1991)
Essential to achieving better relationships among people and for the success of organizations, is feedback. In order to effectively relate to other people we need to know something about the way we are affecting and inﬂuencing them. Feedback provides a way in which we can evaluate this impact. If we are interested in changing an organization in some way, or to evaluate the activities of the organization, feedback can provide us with a fuller understanding of how we are doing or how we should change.